The Contribution of Members of the PKB Fraction in the Lamongan Regency DPRD to the Collection of Community Aspirations - Savira Shofi Yohana (Universitas Negeri Yogyakarta, 2025)
The Regional Representative Council is a representative body at the regional level. It is one of the forms of regional government that has the authority, rights, and obligations to administer its regional government, particularly within its electoral district, to meet the needs of its people. As members of the DPRD, they must also be able to accommodate, absorb and gather the aspirations of the people in their region. The purpose of this study is to analyse the role of Lamongan DPRD members, particularly those from the PKB faction, in absorbing the people's aspirations and to identify the factors that support and hinder the absorption of these aspirations. A qualitative research method was employed, utilising a descriptive approach, which involved collecting data through interviews and observations. The results of this study indicate that the role of PKB faction DPRD members in Lamongan Regency in absorbing community aspirations is carried out through various mechanisms, namely through recesses, working visits, and informal activities. The commitment of Council members and community participation influences the supporting factors. Meanwhile, the inhibiting factors indicate budget and time constraints.